Total neoadjuvant chemoradiotherapy plus anti PD-1 for mid-to-low locally advanced rectal cancer: study protocol of a prospective, single arm, phase II study (STARS - RC06) - Gu, Meichen; Guo, Yuchen; He, Liang; Sun, Xuan; Liang, Tingting; Wang, Zhuo; Li, Ying; Liu, Zheng; Wang, Jingyu; Qiu, Xiang; Guo, Liang; Chang, Pengyu; et al. (Frontiers in Oncology, 2025)
BackgroundNeoadjuvant chemoradiotherapy has become the standard treatment for mid-to-low location LARC. Recently, total neoadjuvant therapy (TNT) has been used in patients with ‘high-risk’ or ‘very high-risk’ LARC according to ESMO guideline (2017). TNT not only increases the pathological complete response (pCR) rate, but also provides patients with more opportunities to preserve organ function. However, TNT mode seems to have reached a plateau. Some clinical studies published in recent years have also confirmed that different modes of neoadjuvant chemoradiotherapy combined with ICIs can further improve the pCR rate to varying degrees. It is necessary to explore an appropriate treatment mode for patients with mid-to-low location, who are unresectable or difficult to achieve R0 resection at the initial stage of surgery and have a strong desire to preserve anal cavity. Numerous basic researches have demonstrated that radiotherapy can remodel the tumor immune microenvironment and play a potential synergistic effect on ICIs. Therefore, this study will aim to explore whether TNT combined with ICIs could improve pCR rates in patients with ‘high-risk’ or ‘very high-risk’ LARC.MethodsThis prospective, single-center, single-arm phase II trial aims to assess the pCR rate of neoadjuvant long-course concurrent chemoradiotherapy sequential 6 cycles CapeOX regimen combined with sintilimab in ‘high-risk/very high-risk’ LARC patients with mid-to-low location and with pMMR phenotype. The primary endpoint for this study is the pCR rate. Secondary endpoints include 2-year sustained of clinical complete response (cCR) rate; CR rate (the rate of patients with sustained cCR for 2 years and pCR); major pathological remission; neoadjuvant rectal score; 3-year non-regrowth disease free survival; 3-year disease-free survival; 3-year overall survival; 3-year localized recurrence-free survival; 3-year distant metastasis free survival; 3-year stoma-free survival, anal sphincter preservation rate; surgical R0 resection rate and safety (adverse events during neoadjuvant therapy and 30 days after surgery, as well as tolerance).DiscussionThis study will investigate whether neoadjuvant long-course concurrent chemoradiotherapy sequential total neoadjuvant chemotherapy combined with immunotherapy could further enhances tumor pCR rate in ‘high-risk/very high-risk’ LARC patients with mid-to-low location and with pMMR phenotype and is expected to improve prognosis.Trial registrationClinicalTrials.gov NCT05998122.